Dualities of Latin America - Katz, Claudio Isaac (2015)
Determining whether the current situation of Latin America is better described as "post-neoliberalism" or as "commodities consensus" requires an analysis of recent changes in the region. Capitalism has expanded in agriculture and mining, accentuating the preeminence of basic exports. Traditional industry is declining, and remittances and tourism have increased in importance. Local capitalists associated with foreign corporations have replaced the national bourgeoisie, while the exodus of peasants consolidates labor precariousness, poverty, and inequality. At the same time, the United States is deploying troops to reorganize its domination. The South American rebellions have limited neoliberal aggression and achieved unusual victories in other parts of the world. The concept of post-neoliberalism emphasizes the region's political turn toward autonomy but overlooks the persistence of the economic model generated during the previous phase. The opposing concept, commodities consensus, highlights the extractivism prevailing throughout the region but plays down the extreme divergences among right-wing, center-left, and radical governments in all other areas. Both concepts contain part of the truth, but neither fully explains the regional scenario.